Small and Medium Enterprises & Artificial Intelligence: A Systematic Literature Review - Ankita, Singh; G.P., Sahu (INTI International University, 2025)
The growth of the world is incredibly reliant on small and medium-sized enterprises (SMEs) that promote innovation. SMEs are also challenged by a shortage of resources, stiff competition and intricate market environments. To a greater extent, they are surmounting these hurdles by using Artificial Intelligence (AI) and Machine Learning (ML) technologies to streamline the work of laborers, make better decisions and enrich customer experience. The research on how AI and ML integrate in SMEs and their effects on business performance will be explored. The body of the present study relied on a systematic literature review methodology designed to estimate the advantages, constraints, and use of AI and ML in 4 major business areas: supply chain management, marketing, finance, and customer service, and ethical and social implications. The moral and social impacts of all the above can be mentioned regarding how AI and ML contribute to SMEs' competitiveness and sustainability. With the help of successful case studies and the results of the literature research, this paper reveals how AI and ML promote innovation and sustainable growth. Despite the numerous advantages, barriers including technological ignorance, costly implementation, and privacy and protection of information are challenges impeding the SMEs. To eliminate such problems, the paper gives great attention to cooperation with the providers of technology, personnel education, and attention to data security. The study is part of the literature about AI and ML implementation within the SME sector since it specifies the key strategies to succeed in any competitive environment